Growth curves of coffee fruits Obatã IAC 1669-20 in different alignments planting - Da Cunha, Antonio Ribeiro [UNESP]; Volpe, Clovis Alberto [UNESP] (Universidade Estadual de Londrina, 2011)
The growth of the coffee fruit is highly dependent on physiological and environmental factors. Environmental factors that most influence the yield of coffee during the critical growth stages are the minimum and maximum temperatures of air, which are affected by solar radiation and depend on the apparent path of the sun. This research work correlated dry mass versus fresh mass, and, fresh and dry mass as function of days after flowering of fruit coffee cv. Obatã IAC 1669-20 planted in three different alignments based on the apparent trajectory of the sun, in Jaboticabal, SP. The planting was aligned according to the apparent path of the sun. There were three treatments with four replications, a total of twelve plots, each plot with one hundred plants of coffee, each treatment corresponded to an alignment of planting. The three alignments used showed no differences with respect the average fresh and dry mass. The growth rate of fruit, in fresh weight, was higher in the exponential phase, and in dry mass was higher in the linear stage. The dry weight (DW) can be estimated from the fresh weight (FW) using the model: DW = A1*exp(FW/t1). The sigmoidal model that represents the fruit growth in of coffee plants in fresh and/or dry mass in terms of days after flowering (DAF) was: FW(DW) = A2+[(A1-A2)/(1+exp(DAF-x0)/dx)].À Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP) pela bolsa de Pós-Doutorado concedida para a realização do referido trabalho.
Curvas de crescimento do fruto de cafeeiro cv. Obatã IAC 1669-20 em diferentes alinhamentos de plantio
Keywords: Coffea arabica L; Fresh and dry fruit weight; Modeling